STUDI KOMPARATIF MINAT BELAJAR SISWA PADA KELUARGA DEMOKRATIS DAN OTORITER - Qamariyatul, Sitti (Jurnal Citra Pendidikan, 2025)
This study aims to describe students' learning motivation in terms of parenting styles that are free demo for parents. Motivation has a very significant role in determining the results of the learning process. Motivation is something that can affect student learning outcomes. This research is a type of qualitative descriptive research. The data collection technique used was observation and interview. The informants in this study were students of the SMK As-Salafiyah Sumberduko Pamekasan. The results show that the findings obtained in this study, where the hypothesis has been tested and tested in learning, the following research can be carried out: Motivation to learn from democratic parenting is high category.